Perbandingan Ketebalan Insulasi Jenis Kertas Laminasi Ditinjau dari Tegangan Tembus Transformator pada Dua Kondisi - Samsurizal, Samsurizal; Afrianda, Rio; Makkulau, Andi (Universitas Sultan Ageng Tirtayasa, 2024)
An insulation layer is used to cover the transformer winding in a transformer. Commonly used insulations in transformers include oil insulation and paper insulation. Paper insulation is soft and flexible, adapting to any desired shape. The crucial factors to consider in insulation are strength and durability. This research was conducted through testing with two conditions: varying the thickness of the paper and the condition of the paper when dried and immersed in insulation oil. The test results show that insulation paper with a thickness of 1.04 mm in a dry state has an average breakdown voltage of 6.7 kV. When immersed in oil, the same thickness has a breakdown voltage of 23.82 kV, indicating that insulation paper with the immersion method has a better breakdown voltage than dry insulation paper.